EXERCISE BEHAVIORS OF PEOPLE IN SURATTHANI MUNICIPALITY, MUANG DISTRICT, SURATTHANI PROVINCE - Chaiklang, Yanothai; Choeychom, Kongkiat; Tengku Sulaiman, Raja Syed (Academic Journal of Thailand National Sports University, 2022)
The purposes of this research were to study and compare the exercise behaviors of people in Suratthani Municipality , Muang District , Suratthani Province , Which are classified by gender and status. The sampees from Suratthani Municipality, Muang District, Suratthani Province with the total of 400 participants. which were randomly selected by accidental sampling method. the data collection tool was a questionnaire consisted of checklist and ratting scales and open-ended questionnaire. In this research, the IOC index of content validity was 0.83. The total reliability of the question was shown by the alpha coefficient of cronbachs was 0.89. The statistics for data analysis consisted of frequency, percentage, mean, standard deviatia, t-test and One-way ANOVA. Based on the analysis of the data gathered, the two findings presented as follows: 1. Most of the people of Surat Thani Municipality, Surat Thani Province, accessed to the exercise by television, newspaper and internet system respectively. Most of them an ticipated in the exercise activities Because of they enjoy and suitable for their health respectively Apart from that this study also found that the difficulty, time and lack of exercise equipment respectively were the problems of their exercise. 2. Male and female and had significant difference access to exercise and exercise method at .05 level, while problems and barriers of exercise was no significant difference. 3. People of different statuses had access to exercise, exercise method, the problems and obstacles of exercise were significantly different at the .05 level. while problems and barriers of exercise was no significant difference. Keywords : Behaviors, Exercise , Suratthani Municipality